2008
DOI: 10.1590/s1677-55382008000300010
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic diagnosis and treatment of nonpalpable testis

Abstract: Introduction: Treatment of the cryptorchid testicle is justified due to the increased risk of infertility and malignancy as well as the risk of testicular trauma and psychological stigma on patients and their parents. Approximately 20% of cryptorchid testicles are nonpalpable. In these cases, the videolaparoscopic technique is a useful alternative method for diagnosis and treatment. Materials and Methods:We present data concerning 90 patients submitted to diagnostic laparoscopy for impalpable testicles. Forty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 20 publications
3
46
0
7
Order By: Relevance
“…In 2013, diagnostic laparoscopy is almost always the approach of choice when attempting to localize a nonpalpable cryptorchid testicle thought to be potentially located in the abdomen. As evidence, all but 1 of the studies in our review published in the past 5 years that included assessment of the abdomen fora nonpalpable testicle 28,32,[36][37][38]43,47,51 used laparoscopy for this part of the procedure, even if they used an open technique to repair the cryptorchidism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, diagnostic laparoscopy is almost always the approach of choice when attempting to localize a nonpalpable cryptorchid testicle thought to be potentially located in the abdomen. As evidence, all but 1 of the studies in our review published in the past 5 years that included assessment of the abdomen fora nonpalpable testicle 28,32,[36][37][38]43,47,51 used laparoscopy for this part of the procedure, even if they used an open technique to repair the cryptorchidism.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies were judged good quality, 27,45,49,52 1 fair quality, 32 and the remainder poor quality. [28][29][30][31][33][34][35][36][37][38][39][40][42][43][44][46][47][48]50,51,53 Eleven studies reported outcomes after either 1-stage FS orchiopexy, 2-stage FS orchiopexy, or primary orchiopexy. [36][37][38][39][40][42][43][44][45]47,48 Nine of these studies, all retrospective cohorts, provided success rates by surgical procedure, although the choice of surgical method is made clinically and not with the intent of comparative effectiveness.…”
Section: Effectiveness Of Surgical Proceduresmentioning
confidence: 99%
“…50 The laparoscopic FS orchidopexy entails division of the gonadal vessels and cremasteric collaterals during advancement of the IAT medial to the inferior epigastric vessels or obliterated umbilical artery. Despite its widespread use, [51][52][53][54] either as a one-or two-stage procedure, atrophy rates can be as high as 33%, probably due to failure of developing adequate collateral blood supply through the deferential artery. The presence of a long looping vas deferens may increase this risk, especially when the procedure is done laparoscopically.…”
Section: Fowler-stephens Orchidopexymentioning
confidence: 99%
“…We carried out a literature analysis aimed at finding the main scientific evidences about the process: we examined some of the main articles related to the topic stored in the Database PubMed 7 , as [45,46,47,48,49,50,51,52] and also the Guidelines of the European Association of Urology (EAU). 8 Based on this information, we designed the corresponding Declare model.…”
Section: Case Studymentioning
confidence: 99%